2021
DOI: 10.4314/tjpr.v20i10.17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of citalopram combined with mindfulness-based stress reduction on symptoms, cognitive functions and self-confidence in patients with depression

Abstract: Purpose: To investigate the impact of the combination of citalopram and mindfulness-based stress reduction (MBSR) on the symptoms, cognitive functions and self-confidence of patients with depression.Methods: A total of 98 patients with depression were selected as study subjects and divided into combination therapy group (CT, n = 51) and conventional group (C, n = 47. The conventional group was treated with citalopram, while the combined group was treated with a combination of citalopram and MBSR. Depressive sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For example, N ‐acetyl‐ D ‐glucosamine is used to enhance the function of the human immune system and treat malignant tumors, inflammation, and joint pain 39 . D ‐Psicose is used to treat high blood sugar, 40 citalopram is capable of curing depression, 20 and alprenolol is used against hypertension and arrhythmia 41 . Therefore, it is important to analyze these metabolites to evaluate the nutritional and medicinal value of cultured O. gracilis fruiting bodies and aerial mycelia, as well as their potential as substitutes for natural O. gracilis .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, N ‐acetyl‐ D ‐glucosamine is used to enhance the function of the human immune system and treat malignant tumors, inflammation, and joint pain 39 . D ‐Psicose is used to treat high blood sugar, 40 citalopram is capable of curing depression, 20 and alprenolol is used against hypertension and arrhythmia 41 . Therefore, it is important to analyze these metabolites to evaluate the nutritional and medicinal value of cultured O. gracilis fruiting bodies and aerial mycelia, as well as their potential as substitutes for natural O. gracilis .…”
Section: Resultsmentioning
confidence: 99%
“…Untargeted metabolomics simultaneously detects as many metabolites as possible to provide a comprehensive chemical overview of a sample, which is employed to analyze bioactive components of fungi. In particular, ultra‐performance liquid chromatography coupled with tandem mass spectrometry (LC‐MS/MS) is commonly used for unbiased investigations of global metabolite profiles, due to its sensitivity and large dynamic range 19–21 . Studies have shown that untargeted metabolomics by LC‐MS/MS is suitable for analyzing Cordyceps metabolomic profiles among species, under both natural and cultivation conditions 22,23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation